2012
DOI: 10.1055/s-0031-1291448
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of endoscopic submucosal dissection for colorectal neoplasia: a systematic review

Abstract: ESD appeared to be an extremely effective technique to achieve R0 resection of large colorectal lesions. The very low rate of surgery for complications also shows the potential safety of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
199
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(216 citation statements)
references
References 13 publications
8
199
2
7
Order By: Relevance
“…Tis-Tumore) und Submukosakarzinomen erschwert [533]. Vergleichende retrospektive und daher nicht randomisierte Studien der ESD mit der EMR gibt es ebenfalls nur aus Fernost [534 -540].…”
Section: Polypektomiedurchführungunclassified
“…Tis-Tumore) und Submukosakarzinomen erschwert [533]. Vergleichende retrospektive und daher nicht randomisierte Studien der ESD mit der EMR gibt es ebenfalls nur aus Fernost [534 -540].…”
Section: Polypektomiedurchführungunclassified
“…If SNNS is clinically developed as a safe surgical approach based on the findings obtained, the clinical application of SNNS will be extensively extended among patients with early gastric cancer. Furthermore, advances have been made in endoscopic treatments for patients with early malignancies, including gastric cancer 35, 36. Therefore, ESD with laparoscopic SBD may become the ultimate stomach‐preserving surgery for avoiding lymph node recurrence in selected patients with extended indications for ESD; however, further studies are needed prior to its expansion as a surgical approach.…”
Section: Future Prospects For Snns As a Minimally Invasive Approachmentioning
confidence: 99%
“…Saito et al consider ESD indicated in LST-G mixed larger than 3 cm (42). Other indications for ESD include mucosal lesions with submucosal fibrosis secondary to prior resections, biopsies or associated with inflammatory bowel disease (43). In those cases, the risk of perforation or leaving a residual lesion is higher if ESD is not performed.…”
Section: Colon and Rectummentioning
confidence: 99%